PENGARUH KECERDASAN EMOSIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Fahira, Keke Tamara; Yasin, Rozaq Muhammad (Jurnal Ilmiah Manajemen & Bisnis, 2021)
The Business sector is facing intense competition around the world so that organizations recognize the importance of human resources as a competitive advantage. For this reason, the factors that have an influence on employee performance are discussed in this study including emotional intelligence, work environment and job satisfaction. This study aims to analyse the effect of emotional intelligence and work environment on employee performance through job satisfaction as intervening variable at PT. Indomaju Textindo Kudus. The quantitative method used in this research is using AMOS confirmatory analysis followed by Structural Equation Modeling (SEM). This research uses non probability sampling method (accidental sampling) in order to collect data. Primary data is used in the study by distributing 150 sample questionnaires to production employees at PT. Indomaju Textindo. The findings in this study are that emotional intelligence and work environment have a direct effect on employee performance. From the research results it can be concluded to improve the performance of employees at PT. Indomaju Textindo can be pursued by maintaining and improving the emotional intelligence of employees and a safe and comfortable work environment.